Valproic acid reprograms the metabolic aberration of cisplatin treatment via ALDH modulation in triple-negative breast cancer cells - Granit Mizrahi, Avital; Gugenheim, Ahinoam; Hamad, Haneen; Hamed, Roa’a; Tetro, Nino; Maimon, Ofra; Khutsurauli, Salome; Nechushtan, Hovav; Nisman, Benjamin; Duran, Deborah; Samman, Widad; Birimberg-Schwartz, Liron; et al. (Frontiers in Cell and Developmental Biology, 2023)
We recently demonstrated that the histone deacetylase (HDAC) inhibitor valproic acid (VPA) reprograms the cisplatin-induced metabolome of triple-negative breast cancer (TNBC) cells, including a shift in hexose levels. Accordingly, we here tested the hypothesis that VPA alters glucose metabolism in correlation with cisplatin sensitivity. Two triple-negative breast cancer cell lines, MDA-MB-231 (a cisplatin-resistant line) and MDA-MB-436 (a cisplatin-sensitive line), were analyzed. The glycolysis and oxidative metabolism were measured using the Glycolysis Stress Test kit. Expression of aldehyde dehydrogenases (ALDHs), enzymes linked to drug resistance, were investigated by western blot and real-time PCR analyses. We additionally studied the influence of ALDH inhibition by disulfiram on the viability of MDA-MB-231 cells and on a TNBC patient-derived organoid system. Cisplatin treatment reduced the extracellular acidification rate (ECAR) in MDA-MB-436 cells but not MDA-MB-231 cells, whereas VPA addition increased the ECAR in both cell lines. VPA further reduced the oxygen consumption rate of cisplatin-treated MDA-MB-436 cells, which correlated with cell cycle alterations. However, in MDA-MB-231 cells, the cell cycle distribution did not change between cisplatin/VPA-cisplatin treatments. In both cell lines, VPA increased the expression of ALDH isoform, ALDH1A1, expression. However, only in MDA-MB-231 cells, VPA synergized with cisplatin to augment this effect. Disulfiram sensitized the cells to the cytotoxic effects of VPA-cisplatin combination. Furthermore, the disulfiram-VPA-chemotherapy combination was most effective in TNBC organoids. Our results show that ALDH overexpression may act as one mechanism of cellular resistance to VPA in TNBC, and that its inhibition may enhance the therapeutic efficacy of VPAchemotherapeutic drug combinations.